EFFECT OF RATTAN BARK NANOFIBER MICROSTRUCTURE WITH HIGH ENERGY MILLING METHOD TO QUALITY MECHANICAL BIOCOMPOSITES - F.N. Ferdiyan (Jurnal Biofisika, 2012)
Rattan  bark  fiber  is  waste  of  raw  rattan  production  activities.  It  usually  used  for roofing  houses  and  strap  goods  in  the  traditional  markets.  Rattan  bark  fiber containing about 40% cellulose, which was potential to be used as filler for composite applications.  Nanotechnology  based  nanoparticles  with  High  Energy  Milling  (HEM) has been applied in this research to find the optimum particle size to be implemented as automotive component filler. Three HEM has been applied (1 hour, 5 hours, and 10 hours), and without HEM (0 hours) as control. Measurable particle size is the size of the single particle. Data in the form of  particle size distributions, intensity, number and volume of distribution, so it can  be assumed to describe the overall condition of the sample. The result shows that 5 hours milling produce the smallest particle size (16.22 nm) and  z averages (129.78 nm). Particle Size Analy zer (PSA) results was related to the Scanning Electron Microscopy (SEM) images of 5 hour milling, particle become smaller and look the same or homogeneous as balls. These results  indicate that the cellulose in the form of three-dimensional nanoparticles is spherical, and the mechanical tests show that biocomposite rattan bark fiber performance was highest among  the  other  natural  composites  (kenaf,  acacia,  water  hyacinth,  banana, coconut).